1989
DOI: 10.1002/polb.1989.090270412
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and dilation in poly(ethyl methacrylate)–carbon dioxide system

Abstract: Sorption and dilation in the system poly(ethyl methacrylate) (PEMA) and carbon dioxide are reported for pressures up to 50 atm over the temperature range 15–85°C. The sorption isotherms were obtained gravimetrically. The dilation accompanying sorption was measured directly with a cathetometer. At low temperatures the sorption and dilation isotherms were concave toward the pressure axis in the low‐pressure region and turned to convex with increasing pressure. As the experimental temperature approached and excee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 18 publications
4
83
0
1
Order By: Relevance
“…These values are reported in Table V at infinite dilution. Similar to previous reports, 31 the polymer compressibility term usually introduces a negligible contribution to eq. (15) for more soluble gases and vapors (e.g., CO 2 , C 2 H 6 , C 3 H 8 , etc.).…”
Section: Figuresupporting
confidence: 65%
“…These values are reported in Table V at infinite dilution. Similar to previous reports, 31 the polymer compressibility term usually introduces a negligible contribution to eq. (15) for more soluble gases and vapors (e.g., CO 2 , C 2 H 6 , C 3 H 8 , etc.).…”
Section: Figuresupporting
confidence: 65%
“…The same phenomena (an increase of the partial molar volume with temperature) has been reported by Kamiya et al in polybutadiene 34 and in poly(ethyl methacrylate). 35 In contrast, Weiss has found that for carbon dioxide in water no significant variation in the partial molar volume was observed as a function of temperature (range 12-40°C) and pressure (range 25-500 atm). 36 The invariant value was 32.3 Ϯ 0.5 cc/mole.…”
Section: 232mentioning
confidence: 90%
“…The measurement of the T g of polymer in compressed CO 2 using high pressure DSC requires the sample exposing to compressed gas for enough time to reach equilibrium at a certain temperature and pressure followed by carrying out the heating or cooling runs. However, the equilibrium CO 2 concentration varies depending on the DSC program temperature, which decreases with an increase in temperature [22,30]. Parker et al [31] investigated the T g of PLA in CO 2 using geometry measurement.…”
Section: Sorption Behavior and Co 2 -Induced Crystallizationmentioning
confidence: 98%